Carotid Duplex Ultrasound Findings in Patients with Coronary Artery Disease (CAD)- A Study in 50 Cases - Bari, MS; Kabir, MS; Ali, MA; Alam, SAN; Majumder, AAS; Mohibullah, AKM; Islam, MN (Cardiovascular Journal, 2011)
Background: Patients with angina pectoris or myocardial infarction are more likely to experience stroke. Ischaemic stroke has been found to develop in approximately 2-5% of patients in the first 1- 2 weeks after myocardial infarction Methods: Fifty patients with coronary artery disease admitted to the National Institute of Cardiovascular Diseases (NICVD), Dhaka, were screened for presence of carotid atherosclerosis by duplex ultrasound study during the period of July 98 to August 98. Results: Carotid lesion were found in 34 patients (68%) and normal carotids found in 16 patients (32%). Age range of patients with and without carotid lesions was 56±5.39 yrs and 47±7.91 yrs respectively. Out of 34 patients, 30 were male (88.2%) and 4 were female (11.7%). 29 patients (85.3%) were smokers, 22 patients (64.7%) were hypertensive and 9 patients (26.4%) were diabetic. Dyslipidaemia was found in 16 patients (47%) and a history of transient ischaemic attack (TIA) was found in 10 patients (29.4%). A coexistent CAD on coronary (CAG) was found in 31 patients (91.1%). Conclusion: Cortaid duplex ultrasound study findings of atherosclerotic lesions in Carotid arteries are good predictors of CAD. Keywords: Carotid atherosclerosis, Carotid duplex ultrasound, Coronary artery disease. DOI: http://dx.doi.org/10.3329/cardio.v1i1.8203 Cardiovasc. j. 2008; 1(1) : 44-47